L’argumentation au banc d’essai d’une théorie métalinguistique - Zsuzsa Simonffy (Corela)
These reflections about the epistemological and methodological framework of linguistic theories are working in the name of effectiveness of linguistic theorising, in order to evaluate them upon the argumentation. It is a very special case that linguistic theory and meta-theory appear to coincide just because both make use of the argumentative structure as a system of representation: the first uses argumentation for the representation of meaning, the second for the representation of theorization. If in our linguistic analyses we are using argumentation as a representational system of meaning, in the evaluation of theories we make use of argumentation as the representational system of the theory itself. Is it possible to avoid assimilating the two, theory and meta-theory? Is assimilation a real danger here? How can the two kinds of argumentation be kept separate and utilized at the same time?